2014
DOI: 10.1160/th13-06-0508
|View full text |Cite
|
Sign up to set email alerts
|

Third generation P2Y12 antagonists inhibit platelet aggregation more effectively than clopidogrel in a myocardial infarction registry

Abstract: The current standard of antiplatelet therapy of patients after myocardial infarction includes the P2Y12 receptor antagonists clopidogrel, prasugrel or ticagrelor. This study aimed to compare the antiplatelet effect of clopidogrel, prasugrel and ticagrelor in patients after myocardial infarction. In a single-centre registry the antiplatelet effect of clopidogrel, prasugrel and ticagrelor was investigated by aggregometry in patients after myocardial infarction. To assess the overall capacity of platelet aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…Numerous factors can influence the extent of platelet inhibition by clopidogrel [ 15 , 16 ]. Some of these factors are assay-dependent [ 13 ], which is also partly evidenced by the present study’s results. For example, presence of diabetes and proton pump inhibitor medication appeared to be more strongly associated with ADP-induced aggregation than with r-ADP-agg.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Numerous factors can influence the extent of platelet inhibition by clopidogrel [ 15 , 16 ]. Some of these factors are assay-dependent [ 13 ], which is also partly evidenced by the present study’s results. For example, presence of diabetes and proton pump inhibitor medication appeared to be more strongly associated with ADP-induced aggregation than with r-ADP-agg.…”
Section: Discussionsupporting
confidence: 80%
“…However, Iyu et al recently found that P2Y 12 -antagonists produced only minor additional inhibition of TRAP-induced aggregation and found no evidence that any of the P2Y 12 -antagonists act through other G-protein receptors including PAR1 [ 22 ]. Results from our group comparing different P2Y 12 -inhibitors showed that there are no differences of the TRAP-induced platelet aggregation in the corresponding medication group [ 13 ]. Although controversial findings exist on the influence of P2Y 12 -inhibitors TRAP-induced aggregation might be a reasonable internal control for patients under clopidogrel medication, as also stated by Gremmel et al in 2010 [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of platelet purinergic receptors in the context of platelet aggregation has been well documented with co-stimulation of the P2Y1 and P2Y12 receptors by ADP, and following ATP stimulation of the P2X1 receptor [15][16][17][18][19][20][21][22]. Furthermore, a number of studies have detailed the ability of purinergic receptor stimulation to induce increases in P-selectin expression and the incidence of platelet-leukocyte conjugates which are considered to be a prerequisite for leukocyte recruitment [23][24][25].…”
Section: Introductionmentioning
confidence: 99%